Analysis of Factors Affecting Subjective Fatigue in Hospital Nurses: A Study in the Inpatient Installation - Annisa Rizki Kautsar; Winarko; Rusmiati Rusmiati; Hadi Suryono; Suprijandani; Cahyo Widoko Laksono (POLTEKKES KEMENKES PONTIANAK, 2024)
Fatigue can cause a decrease in worker productivity, especially in human service professions, one of which is nursing staff. The purpose of this study was to analyse the factors influencing the occurrence of subjective fatigue in nurses at the inpatient installation of Hospital X Surabaya City. This study applied analytical observations with a cross sectional approach. The sample size was 90 nurses selected by proportional simple random sampling from a population of 109 female nurses in the inpatient installation. Data processing used univariate and bivariate analysis with α = 0.05. The results of this study indicate that there is an influence between work shifts (p = 0.001) and lighting (p = 0.022) on the subjective fatigue of nurses in inpatient installations. While age (p = 0.739), nutritional status (p = 0.206), and working period (p = 0.699) have no effect on the subjective fatigue of nurses in inpatient installations. The conclusion of this study is that work shifts and lighting affect the subjective fatigue of nurses in the inpatient installation of Hospital X Surabaya City. It is recommended to monitor the physical environment, maintain a healthy lifestyle, and proper shift arrangements to prevent fatigue in nurses and improve services.